Investigations on the elasticity of functional gold nanoparticles using single-molecule force spectroscopy. Issue 19 (24th April 2018) - Sun, Li; Riedel, René; Stanciu, Stefan G.; Yang, Fang; Hampp, Norbert; Xu, Li; Wu, Aiguo
Abstract : In this focused review we turn our attention towards several approaches for detecting the elasticity of NPs, systematically summarizing the divergent elasticity values of distinct gold nanoparticles (AuNPs) with different surfaces. Abstract : A wide range of investigation tools and frameworks aimed at the in depth understanding of the physico-chemical properties of different nanomaterials and at exploring their cellular interactions and effects have been reported in the past couple of decades. Among these, Single-Molecule Force Spectroscopy (SMFS) emerges as a very important tool for characterizing nanoparticles (NPs) and one of its very valuable applications consists in the quantitative analysis of the NPs' elasticity. In SMFS experiments that tackle this subject, a sharp tip present on the apex of a cantilever is indented into a single NP, and then the Young's modulus is determined as a measure of its elasticity, which is one of the fundamental mechanical parameters affecting the structural and functional cellular parameters. Based on such approaches, SMFS enables the observation and analysis of significant cellular effects that are relevant to various cellular parameters. In this focused review, we turn our attention towards several approaches for detecting the elasticity of NPs, systematically summarizing the divergent elasticity values of distinct gold nanoparticles (AuNPs) with different surfaces. We carry as well a critical discussion on the elasticity assessment models and the fundamental factors that influence NP elasticity assessment by means of SMFS.